PENGEMBANGAN INTRUMEN PENILAIAN PENDIDIKAN AGAMA ISLAM - Muslihati, Muslihati; Wardan, Khusnul (STAI Sangatta Kutai Timur, 2024)
Effective assessment in learning is a key element in determining the success of educational goals. This study aims to explore more deeply the development of Islamic Religious Education assessment instruments. This study uses a library research approach, meaning that researchers only deal directly with sources available in the library such as articles, books and others, from these data sources researchers present a deep understanding of the development of Islamic Religious Education assessment instruments. The significance and novelty of the development of Islamic Religious Education assessment instruments emphasizes 1) the integration of socio-spiritual attitudes, knowledge, and skills that were previously more focused on the spiritual dimension alone, now shifting the paradigm of Islamic Religious Education learning from a doctrinal approach to an integrative approach that is relevant to the needs of students in the modern era. 2) Emphasis on the implementation of Islamic values ​​in practice, the application of Islamic teaching values is not just a theoretical understanding but also links Islamic Religious Education learning with critical and applicable thinking skills based on the teachings of the Qur'an and Hadith. 3) There is a relationship between character education and Islamic civilization, this strengthens the relevance of learning Islamic Religious Education in the global context and its contribution to building a civilized society.